Social Media Marketing as a Tool for SME Brand Performance; A Study of Selected SMES in Ibadan, Oyo State, Nigeria - Kelechi C. CHUKWUDI; Adewale O. OSIBANJO; Bolanle P. BOLODEOKU; Chijindu I. OKPALAOKA (Communications of International Proceedings, 2021)
This study examined social media marketing as a tool for SME brand performance. The objective of this study was to examine the various concepts of social media marketing and how it drives SME brand performance. The study population of 150 consisted of all employees engaged in the operation of the selected SMEs. The sample size of 109 was arrived at using the random sampling method of Yamane (1967) and primary data was gathered using a well-structured questionnaire. The study used a descriptive type of survey design while t-statistics was adopted for hypotheses testing. The study analyzed data collected through the use of a statistical package for social sciences (SPSS). The study revealed that social media marketing has a significant effect on the performance of SMEs operating within Ibadan, Oyo State, Nigeria. Given the findings, the study concluded that it is essential for SMEs to understand how to utilize social media to connect with consumers and establish a brand through connections. Additionally, it is critical for effective brand performance, enhancing their ability to adapt to a changing and demanding corporate environment and technology to maximize performance. The study, therefore, recommended that for maximum productivity, employees of the firm must be trained and exposed to social media skills and effective management of the firm's social media accounts; this will improve brand awareness and the level of technology adoption
Keywords: Social Media; Marketing; Small Medium Enterprise (SME); Brand Performance